Fat Oxidation Kinetics Is Related to Muscle Deoxygenation Kinetics During Exercise - Zurbuchen, Anouck; Lanzi, Stefano; Voirol, Ludovic; Trindade, Cybele Barboza; Gojanovic, Boris; Kayser, Bengt; Bourdillon, Nicolas; Chenevière, Xavier; Malatesta, Davide (Frontiers in Physiology, 2020)
Purpose: The present study aimed to determine whether whole-body fat oxidation and muscle deoxygenation kinetics parameters during exercise were related in individuals with different aerobic fitness levels. Methods: Eleven cyclists [peak oxygen uptake (VO2peak): 64.9 ± 3.9 mLxkg-1xmin-1] and eleven active individuals (VO2peak: 49.1 ± 7.4 mLxkg-1xmin-1) performed a maximal incremental cycling test to determine VO2peak and a submaximal incremental cycling test to assess whole-body fat oxidation using indirect calorimetry and muscle deoxygenation kinetics of the vastus lateralis using near-infrared spectroscopy. A sinusoidal model was used to characterize fat oxidation kinetics and to determine the intensity (Fatmax) eliciting maximal fat oxidation (MFO). The muscle deoxygenation response was fitted with a double linear model. The slope of the first parts of the kinetics (a1) and the breakpoint ([HHb]BP) were determined. Results: MFO (p = 0.01) and absolute fat oxidation rates between 20% and 65% VO2peak were higher in cyclists than in active participants (p < 0.05), while Fatmax occurred at a higher absolute exercise intensity (p = 0.01). a1 was lower in cyclists (p = 0.02) and [HHb]BP occurred at a higher absolute intensity (p < 0.001) than in active individuals. VO2peak was strongly correlated with MFO, Fatmax and [HHb]BP (r = 0.65-0.88, p ≤ 0.001). MFO and Fatmax were both correlated with [HHb]BP (r = 0.66, p = 0.01 and r = 0.68, p < 0.001, respectively) and tended to be negatively correlated with a1 (r = -0.41, p = 0.06 for both). Conclusion: This study showed that whole-body fat oxidation and muscle deoxygenation kinetics were both related to aerobic fitness and that a relationship between the two kinetics exists. Individuals with greater aerobic fitness may have a delayed reliance on glycolytic metabolism at higher exercise intensities because of a longer-maintained balance between O2 delivery and consumption supporting higher fat oxidation rates.